Export Competitiveness of Indonesia’s Uncoated Paper in the Global Forest Products Market During and After the COVID-19 Pandemic: Evidence from Constant Market Share Analysis - Elisa Ganda Togu Manurung; Bintang Charles Hamonangan Simangunsong; Maya Atasha (Jurnal Sylva Lestari, 2026)
Indonesia is one of the world’s leading exporters of uncoated paper products, supported by abundant plantation forests. However, Indonesia's uncoated paper export declined over the period 2018-2024. The objective of this research was to examine factors affecting the export competitiveness of Indonesia’s uncoated paper products in the global forest products market during and after the COVID-19 pandemic. Data on export values, exchange rates, and GDP deflators obtained from Trade Map and the IMF were analyzed using the Constant Market Share analysis.  The results showed that during the COVID-19 pandemic, Indonesia’s uncoated paper exports increased mainly due to favorable impacts on world trade and competitiveness. In contrast, the composition of commodities and market distribution had an unfavorable impact on Indonesia’s exports. After the COVID-19 pandemic (2023-2024), Indonesia’s uncoated paper exports declined due to adverse effects on global trade and a negative competitiveness effect. On the other hand, commodity composition and market distribution had a favorable impact on Indonesia's exports. For the future, Indonesia needs strategies to maintain and improve the competitiveness and market stability of HS 480256, HS 480255, and HS 480257, such as: ensuring the forest certification; maintaining sustainable production, periodically reviewing international trade barriers, tariff changes, production cost efficiency; and increasing the capacity and technology of paper products. To provide more insight, the CMS method should be combined with an econometric method that can directly model a structural change in demand and estimate important parameters, such as price, cross-price, and income elasticities. Keywords: competitiveness effect, composition effect, constant market share, market distribution effect, writing paper